Behavioral Analysis of Health Service use of the Ilaga Community Health Center, Puncak Regency Central Papua Province - Wonda, Frengky Lani; Zainuri, Agus; Togodly, Arius; Tingginehe, Rosmin M.; Ruru, Yacob; Rantetoding, Septevanus (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze utilization behavior service health, Ilaga District Community Health Center, Puncak Regency, Central Papua Province. The type of research used is descriptive qualitative. Data was obtained using interviews and analyzed qualitatively. The results of the research showed that people seeking treatment in the Ilaga District used the Community Health Center as a place for treatment and as a referral place to other health service institutions (referrals) so that the community was enthusiastic in utilizing the Community Health Center services. Not all people have health insurance due to low knowledge and lack of support from health workers in assisting health services in arranging membership for the National Health Insurance Social Security Administering Body (BPJS). Security disturbances disrupt the accessibility of community health services in the event of conflict, especially from armed criminal groups.